Incorporation of D-amino Acids and Ornithines into Tirzepatide by Biosynthesis in E. Coli - Yanli Xu; Yuxin Fu; Oscar P. Kuipers (International Journal of Peptide Research and Therapeutics, 2026)
Purpose Tirzepatide is an effective dual GLP-1 and GIP receptor agonist for type 2 diabetes and obesity but faces challenges with low oral bioavailability and stability. Currently, tirzepatide is produced industrially via solid-phase peptide synthesis (SPSS), allows incorporation of noncanonical residues but limited in scalability for rapid mutant generation and biological delivery strategies. This study aimed to develop a microbial biosynthetic platform for tirzepatide production to enable efficient mutant library construction and stability optimization. Methods A ribosomal synthesis and post-translational modification (RiPP)-based microbial expression system was engineered for tirzepatide biosynthesis. Ornithine residues were introduced at positions 2 and 13 through enzymatic arginine conversion. Co-expression of the RiPP-associated enzyme OspD enabled incorporation D amino acids. Structural characterization was conducted using circular dichroism spectroscopy, and peptide stability was evaluated in human serum. Results The engineered system successfully produced tirzepatide and its designed mutants. Site-specific ornithine incorporation and D amino acid modifications were achieved. Circular dichroism analysis revealed structural alterations in the modified peptides. Human serum assays demonstrated that the engineered mutants remained stable for at least two days, indicating proteolytic resistance. Conclusion This work establishes a feasible microbial RiPP-based strategy for tirzepatide biosynthesis, providing a foundation for rapid mutant generation, structural optimization, and development of microbial-based peptide delivery systems.